IDDF2019-ABS-0135 Pharmacokinetics of once-daily sofosbuvir or ledipasvir/sofosbuvir in HCV-infected pediatrics aged 3 to. (June 2019) - Begley, Rebecca; Meng, Amy; Massetto, Benedetta; Shao, Jiang; Sze Man Yip, Christina; Ling, John; Mathias, Anita
Abstract : Background: SOF 400 mg and LDV/SOF 90/400 mg are approved HCV treatment in adults and adolescents. Pharmacokinetic (PK) data indicates that SOF 200 mg and LDV/SOF 45/200 mg are appropriate doses in children 6 to <12 years old (y). SOF and LDV/SOF oral granules were developed; PK was assessed in children 3 to < 6 y. Methods: HCV-infected children (3 to <6 y) received SOF or LDV/SOF with doses selected to target exposures similar to adults: subjects ≥17 kg received SOF 200 mg or LDV/SOF 45/200 mg; subjects <17 kg received SOF 150 mg or LDV/SOF 33.75/150 mg, QD. Subjects received SOF+RBV 12 or 24 weeks (GT2 or GT3, respectively) or LDV/SOF 12 weeks (GT1, 4). Intensive PK sampling (IPK lead-in) was performed on Day 7 (SOF; N=11) or 10 (LDV/SOF; N=15). Exposures (AUCtau and Cmax) from subjects were compared to exposures in Phase 2/3 adult clinical programs. The primary endpoint was AUCtau of GS-331007 and LDV with predefined PK equivalence bounds of 50–200%. Results: All but 1subject completed IPK assessments. At baseline, median age and weight for subjects was 5 y and 17 kg in SOF+RBV PK lead-in (N=11) and 5 y and 20 kg in LDV/SOF subjects (N=14). The predefined PK criteria were met as GS-331007 and LDV AUCtau were within the 50–200% boundaries as compared with the adult Phase 2/3 population (table 1 ). The GS-331007 Cmax (SOF+RBV) was modestly higher; these increases are not considered clinically relevant based on established exposure-safety analyses. SOF concentrations were within the range of those observed in the SOF and LDV/SOF adult Phase 2/3 population (data not shown). Conclusions: SOF 200 or 150 mg or LDV/SOF 45/200 or 33.75/150 mg, for subjects ≥17 kg or <17 kg, respectively, were well tolerated and provided similar exposures to those observed in adults. These data support the ongoing evaluation of these doses in children 3 to <6 y.